Geochemical data from IODP Expedition 310 Tahiti fossil corals - Ryuji Asami; Thomas Felis; Ryuichi Shinjo; Masafumi Murayama; Yasufumi Iryu (PANGAEA, 2025)
Constraining climate models under extreme boundary conditions of the past on societally-relevant timescales is complicated by a common lack of high-resolution reconstructions of sea surface environmental variability for glacial periods. Fossil corals provide a unique but relatively rare climate proxy for the tropical ocean that can be sampled at high resolution. Here, we present subseasonally-resolved geochemical proxy data (Sr/Ca, δ^1?O, δ^1^3C) from well-preserved fossil corals of the penultimate glacial (153 ka and 148 ka during Marine Isotope Stage 6b) and last glacial periods (30 ka during MIS 3a) drilled by Integrated Ocean Drilling Program (IODP) Expedition 310 "Tahiti Sea Level" in the central tropical South Pacific. Samples from selected well-preserved skeletal portions with no evidence of diagenetic alteration were analyzed at 0.5 mm resolution for geochemistry. These datasets are the first monthly-to-bimonthly resolved coral proxy records of the penultimate glacial and the last glacial periods for the Pacific Ocean, and for the global ocean with respect to the penultimate glacial, which can be useful for paleoclimate reconstruction studies and model simulation studies.